Hospitalists’ perception of their communication with primary care providers – survey results from six hospitals in Central Switzerland - Manuela Käufeler; Patrick E. Beeler; Lena S. Müller; Armin Gemperli; Christoph Merlo; Balthasar L. Hug (Swiss Medical Weekly)
OBJECTIVES: Due to the increasing complexity of the healthcare system, effective communication and data exchange between hospitalists (in-hospital physicians) and primary care physicians (PCPs) is both central and challenging. In Switzerland, little is known about hospitalists’ perception of their communication with PCPs. The primary objective was to assess hospitalists’ satisfaction with their communication with PCPs. Secondary objectives addressed all information about the referral process and communication with PCPs during and after the hospital encounter. Lastly, the results of a previous survey among PCPs were juxtaposed to compare their responses to similar questions.